Impact of BMI for clinical outcomes in Japanese breast cancer patients. (20th January 2020) - Gondo, Naomi; Sawaki, Masataka; Hattori, Masaya; Yoshimura, Akiyo; Kotani, Haruru; Adachi, Yayoi; Kataoka, Ayumi; Sugino, Kayoko; Mori, Makiko; Horisawa, Nanae; Terada, Mitsuo; Ozaki, Yuri; et al.
Abstract: Objective: The relationship between the body mass index (BMI) at the time of breast cancer diagnosis and the prognosis of breast cancer patients has not yet been clarified. We investigated the impact of obesity for clinical outcomes in Japanese breast cancer patients. Methods: Women with primary breast cancer operated between 2002 and 2014 were identified. All patients are categorized into four groups according to BMI. The range of BMI is <18.5 kg/m 2, from 18.5 to 24.9 kg/m 2, 25 to 29.9 kg/m 2, >30 kg/m 2 in underweight, normal, overweight and obesity groups, respectively. The correlation between BMI and overall survival (OS), breast cancer-specific survival (BCSS) and disease-free survival (DFS) were statistically analyzed. Results: From the database of our institution, we identified 3223 patients. The median follow-up period was 57 months (1–149). We categorized 2257 (70.0%), 318 (9.9%), 545 (16.9%) and 103 (3.2%) patients into normal, underweight, overweight obesity groups respectively. There were189 patients (5.9%) deaths due to breast cancer recurrence (137 patients) and other disease (52 patients). Obesity groups was significantly high compared with normal groups for OS (adjusted HR, 2.43; 95% CI, 1.38–4.28; P < 0.001), BCSS (adjusted HR, 2.73; 95% CI, 1.15–6.44; P = 0.02) and DFS (adjusted HR, 1.83; 95% CI, 1.11–3.02; P = 0.017) by multivariate analysis. Especially, OS (adjusted HR, 4.87; 95% CI, 2.15–11.04; P < 0.001), BCSS (adjusted HR, 4.51; 95% CI, 1.52–13.34; P < 0.001) and DFS (adjusted HR, 4.87; 95% CI, 1.02–4.89; P = 0.04) were statistically insignificant in postmenopausal ER-positive breast cancer patients. Conclusion: Obesity might be risk factor for OS, BCSS and DFS, especially postmenopausal ER-positive women. Abstract : Obesity might be risk factors for OS, BCSS and DFS among Japanese breast cancer. In particular, it may be a risk factor for postmenopausal ER-positive women.